ENHANCING STUDENTS INTERACTION THROUGH TEACHER QUESTIONS - Risnawati - (HOLISTICS, 2009)
EFL students are often hesitant to interact in classrooms. Oral questioning is a very powerful way for teachers to interact with students. However, asking questions and responding to answers in classrooms are not always as easy as they seem. For the sake of enhancing students’ interaction, teachers should develop  a repertoire of questioning  skills. This article intends to show that question and answer activities in classroom, if exploited appropriately, can enhance student interaction. Clarity of questions, types of questions, techniques of asking questions, and techniques of responding to answers are respects that influence the quality of student interaction.